If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(v + 6) = -6v + -24 Reorder the terms: -9(6 + v) = -6v + -24 (6 * -9 + v * -9) = -6v + -24 (-54 + -9v) = -6v + -24 Reorder the terms: -54 + -9v = -24 + -6v Solving -54 + -9v = -24 + -6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6v' to each side of the equation. -54 + -9v + 6v = -24 + -6v + 6v Combine like terms: -9v + 6v = -3v -54 + -3v = -24 + -6v + 6v Combine like terms: -6v + 6v = 0 -54 + -3v = -24 + 0 -54 + -3v = -24 Add '54' to each side of the equation. -54 + 54 + -3v = -24 + 54 Combine like terms: -54 + 54 = 0 0 + -3v = -24 + 54 -3v = -24 + 54 Combine like terms: -24 + 54 = 30 -3v = 30 Divide each side by '-3'. v = -10 Simplifying v = -10
| 40x+75=40x+35 | | 15x-7=2x-79 | | 7.5x+0.5x=68.40 | | .3x=.1x+2.9 | | -4w-46=2(w+4) | | 40x+35=40x+35 | | Z+9=84 | | 60=-15n | | X/5=3x-4/10 | | x^7=78 | | 55/x=11/5 | | 5u(-7u^3)= | | 8+2x+2=3x+5 | | 2f+3=7f-24 | | 4x+2(3x-9)=66 | | 11=1/4m-3m | | 7k^2-4k-20=0 | | -1p-5(1p+4)=-25-7p | | (2x=5)/3=y | | 9+4x=-63 | | 2y-12=y-5 | | 110/12 | | 4x^(3/2)=32 | | 14k/9=4k-198 | | 1/7*9/13 | | 15y+(-4)=15y+6 | | 15-3x=3x+15 | | 3k^2-16k+20=0 | | .75y+.5x=11.5 | | .5x+.75y=11.5 | | 2(x-3)+7=11 | | 4x+112x=13 |